A checklist of native freshwater fish from Brantas River, East Java, Indonesia - Veryl Hasan; NoorHidayah B Mamat; Josie South; Felipe Polivanov Ottoni; Maheno Sri Widodo; Prigi Arisandi; Wahyu Isroni; ‪Rikho Jerikho; Dian Samitra; Abdul Rahem Faqih; Charles P. H. Simanjuntak; ‪Akhmad Taufiq Mukti‬ (Society for Indonesian Biodiversity, 2022)
Abstract. Hasan V, Mamat NB, South J, Ottoni FP, Widodo MS, Arisandi P, Isroni W, Jerikho R, Samitra D, Faqih AR, Simanjuntak CPH, Mukti AT. 2022. A checklist of native freshwater fish from Brantas River, East Java, Indonesia. Biodiversitas 23: 6031-6039. This study aims to provide information on the freshwater fish species composition of the Brantas River, the second-largest river in Java, Indonesia. All samples used in this study were the caught activities during Fish Resource Survey (form May 5, 2021 to August 20, 2022). Sampling was carried out in four stations of the Brantas River, representing upstream, the Karangkates Reservoir, midstream, and downstream. This work recorded 42 fish species divided into 35 genera and 21 families. Cyprinidae was the dominant family, comprising 12 genera and 15 species. According to the IUCN Red List, most fish species inhabiting the Brantas River have a conservation status of Least Concern (LC) or Data Deficient (DD), except for Rasbora lateristriata which is categorized as Vulnerable (VU). Genera Tor and Neolissochilus are rarely found in Javanese waters. We suggest that the conservation status of these species should be reviewed. Information on habitat use and ecological interactions of fish occurring in the Brantas River are needed urgently to make appropriate conservation decisions and plans. Therefore, we suggest that more collections need to be carried out in the studied river, as well as studies based on eDNA analysis and research incorporating both morphological and molecular data.